Transcriptional control of embryonic and adult neural progenitor activity - Singh, Niharika; Siebzehnrubl, Florian A.; Martinez-Garay, Isabel (Frontiers in Neuroscience, 2023)
Neural precursors generate neurons in the embryonic brain and in restricted niches of the adult brain in a process called neurogenesis. The precise control of cell proliferation and differentiation in time and space required for neurogenesis depend on sophisticated orchestration of gene transcription in neural precursor cells. Much progress has been made in understanding the transcriptional regulation of neurogenesis, which relies on dose- and context-dependent expression of specific transcription factors that regulate the maintenance and proliferation of neural progenitors, followed by their differentiation into lineage-specified cells. Here, we review some of most widely studied neurogenic transcription factors in the embryonic cortex and neurogenic niches in the adult brain. We compare functions of these transcription factors in embryonic and adult neurogenesis, highlighting biochemical, developmental, and cell biological properties. Our goal is to present an overview of transcriptional regulation underlying neurogenesis in the developing cerebral cortex and in the adult brain.